Generative Modeling for Imbalanced Credit Card Fraud Transaction Detection - Mohammed Tayebi; Said El Kafhali (Journal of Cybersecurity and Privacy)
The increasing sophistication of fraud tactics necessitates advanced detection methods to protect financial assets and maintain system integrity. Various approaches based on artificial intelligence have been proposed to identify fraudulent activities, leveraging techniques such as machine learning and deep learning. However, class imbalance remains a significant challenge. We propose several solutions based on advanced generative modeling techniques to address the challenges posed by class imbalance in fraud detection. Class imbalance often hinders the performance of machine learning models by limiting their ability to learn from minority classes, such as fraudulent transactions. Generative models offer a promising approach to mitigate this issue by creating realistic synthetic samples, thereby enhancing the model’s ability to detect rare fraudulent cases. In this study, we introduce and evaluate multiple generative models, including Variational Autoencoders (VAEs), standard Autoencoders (AEs), Generative Adversarial Networks (GANs), and a hybrid Autoencoder–GAN model (AE-GAN). These models aim to generate synthetic fraudulent samples to balance the dataset and improve the model’s learning capacity. Our primary objective is to compare the performance of these generative models against traditional oversampling techniques, such as SMOTE and ADASYN, in the context of fraud detection. We conducted extensive experiments using a real-world credit card dataset to evaluate the effectiveness of our proposed solutions. The results, measured using the BEFS metrics, demonstrate that our generative models not only address the class imbalance problem more effectively but also outperform conventional oversampling methods in identifying fraudulent transactions.